2015
DOI: 10.1038/nature16044
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of community and facility-based HIV testing to address linkage to care gaps in sub-Saharan Africa

Abstract: HIV testing and counselling is the first crucial step for linkage to HIV treatment and prevention. However, despite high HIV burden in sub-Saharan Africa, testing coverage is low, particularly among young adults and men. Community-based HIV testing and counselling (testing outside of health facilities) has the potential to reduce coverage gaps, but the relative impact of different modalities is not well assessed. We conducted a systematic review of HIV testing and counselling modalities, characterizing facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
532
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(598 citation statements)
references
References 151 publications
36
532
2
1
Order By: Relevance
“…Door-to-door testing and mobile testing strategies have moved testing services out of health facilities and into communities, overcoming barriers related to clinic-based testing and, subsequently, increasing testing coverage. However, despite these advancements, there remains a need for novel interventions that can promote testing among men and other hard-to-reach populations [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Door-to-door testing and mobile testing strategies have moved testing services out of health facilities and into communities, overcoming barriers related to clinic-based testing and, subsequently, increasing testing coverage. However, despite these advancements, there remains a need for novel interventions that can promote testing among men and other hard-to-reach populations [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…7 Many programmes in sub-Saharan Africa, including that described by Ying and colleagues, have very high coverage rates. 8 No other testing approach could diagnose 90% of HIVpositive people more comprehensively. 2 New strategies to link newly diagnosed HIV-positive people to care are necessary.…”
Section: Home Testing and Counselling With Linkage To Carementioning
confidence: 99%
“…Several studies have shown the benefits of meta-analysis in terms of both higher statistical power and precision in detecting differentially expressed genes (DEGs) in different complex traits including infectious disease (Song et al, 2014; Camacho-Cáceres et al, 2015; Sharma et al, 2015; Yin et al, 2015; Wang C.-Y. et al, 2015; Wang X. et al, 2015).…”
Section: Introductionmentioning
confidence: 99%